The Stochastic Volatility of Short‐term Interest Rates: Some International Evidence - Ball, Clifford A.; Torous, Walter N. (Journal of Finance, 1999)
This paper estimates a stochastic volatility model of short‐term riskless interest rate dynamics. Estimated interest rate dynamics are broadly similar across a number of countries and reliable evidence of stochastic volatility is found throughout. In contrast to stock returns, interest rate volatility exhibits faster mean‐reverting behavior and innovations in interest rate volatility are negligibly correlated with innovations in interest rates. The less persistent behavior of interest rate volatility reflects the fact that interest rate dynamics are impacted by transient economic shocks such as central bank announcements and other macroeconomic news.